A CORRELATION OF USING CONTEXT CLUES STRATEGY AND VOCABULARY MASTERY AT THE FIFTH SEMESTER STUDENTS OF INSTITUT PENDIDIKAN TAPANULI SELATAN PADANGSIDIMPUAN - Lollo Rosa Lubis (Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study to know whether there was a significant correlation of using context clue strategy and vocabulary mastery at the fifth semester students of English Department of Institut Pendidikan Tapanuli Selatan. The research was conducted by applying quantitative descriptive with 20 students as the sample and they were taken by using random sampling technique. Questionnaire and test were used in collecting the data. Based on inferential statistics by using r product moment and R square, the result showed ttable was less tcalculated (0.444<0.516) at a significant level of 5% and R square was 0.266470068. It means there was a significant correlation of using context clue strategy on vocabulary mastery at significant level of 5% at the fifth semester students of English Department of Institut Pendidikan Tapanuli Selatan (IPTS) and strategy context clue gave contribution as big as 26,65% on vocabulary mastery.